2020
DOI: 10.3390/app10020551
|View full text |Cite
|
Sign up to set email alerts
|

Thermogram Breast Cancer Detection: A Comparative Study of Two Machine Learning Techniques

Abstract: Breast cancer is considered one of the major threats for women’s health all over the world. The World Health Organization (WHO) has reported that 1 in every 12 women could be subject to a breast abnormality during her lifetime. To increase survival rates, it is found that it is very effective to early detect breast cancer. Mammography-based breast cancer screening is the leading technology to achieve this aim. However, it still can not deal with patients with dense breast nor with tumor size less than 2 mm. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Finally the extracted features are used for the training of various conventional machine learning classifiers like Naï ve Bayes (NB), Support vector machine (SVM), K nearest neighbor (KNN), Random Forest (RF), Decision tree, AdaBoost etc. [24][25][26][27][28][29] to classify the breast thermal images into either normal or abnormal cases. Mostly the accuracies of these machine learning based approaches varies in the range from 92% to 97%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally the extracted features are used for the training of various conventional machine learning classifiers like Naï ve Bayes (NB), Support vector machine (SVM), K nearest neighbor (KNN), Random Forest (RF), Decision tree, AdaBoost etc. [24][25][26][27][28][29] to classify the breast thermal images into either normal or abnormal cases. Mostly the accuracies of these machine learning based approaches varies in the range from 92% to 97%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the outcome of neural network proved that the adopted machine learning model is effective and efficient for both sets of input data as well as it confirmed that it can be more vigorous than the BCRAT. AlFayez et al [22], introduced a thermogrambased breast cancer detection approach. At first, a preprocessing of image was achieved by utilizing top-hat transform, homomorphic filtering in addition to an adaptive histogram equalization.…”
Section: Related Workmentioning
confidence: 99%
“…In the segmentation step, they used a combination of binary masking, k-means clustering, and the signature boundary for the feature extraction step. In another research [42], two methods of classification were used, namely, Multilayer Perceptron (MLP) and Extreme Learning Machine (ELM). In [43], the authors proposed a new automatic segmentation method that consisted of preprocessing, segmentation, and separation for an area of interest and then, segmenting ROI to both right and left breasts.…”
Section: Related Workmentioning
confidence: 99%